Modelos pedagógicos en educación general básica media en la escuela particular Salesiana Don Bosco, sector La Kennedy - Villarreal Vela, Hugo Gustavo (2018)
The importance of the present study is to know the practice of the pedagogical model in the Don Bosco Salesian Private School "Kennedy" of the City of Quito. For which it took into account teachers, students as well as their behavior in relation to their educational work in the General Basic Education. The research seeks to publicize the pedagogical model used by the institution by observing the educational practices used by three coordinating teachers, director and assistant director of the institution. In this way reliable data is obtained about the model used in the institution. Throughout the investigation we will find several theoretical references about the pedagogical models: Traditional, Constructivist and Critical, as well as the methodology of qualitative type taken into account: teaching role, curricular contents, didactic strategies and evaluation. The analysis of the results presents the daily work of the teachers of the institution, the presentation of findings will highlight the relationship that exists between the model of the institution and the curricular update model. The prevalence of the constructivist model is evident in the characteristics of the observation, complementing with data collection instruments the pertinent data about the constructivist model that the institution uses.